Reduction in controlled power switches for a single-phase novel multilevel inverter. Issue 8 (3rd August 2019) - Mahato, Bidyut; Majumdar, Saikat; Jana, Kartick Chandra
ABSTRACT: Multilevel inverter (MLI) generates stepped voltage with appropriate switching combination of power devices, thus restraining the requirement of filter circuit for an efficient power conversion. MLIs are attracting due to some of the major features like economic cost, installation space, bulkiness, complexity along with its enormous applications in industries like cement factory, ceramic industry, aerospace applications etc. In this paper, a single-phase generalised inverter based on five different algorithms is proposed that uses the minimum of overall power components. The presented topology can be used in low and medium voltage applications. To verify the simulation results obtained by MATLAB/Simulink, DS1103 controller is used to generate the corresponding experimental results by developing a prototype model in the laboratory. Nevertheless, a comparative assessment for the different required components of the proposed topology is carried out with some recently developed topologies. Reduction in power switches, driver circuits and DC voltage sources reduces the size, cost, complexity and enhances the overall performance. In addition, level per switch ratio is added in this paper to decide the effectiveness of the proposed topology.